NON-EQUILIBRIUM THERMODYNAMICS WITH THERMAL AND FLUCTUATIONS OF THE VALUES OF STABILITY OF MATERIALS OF PARAMETERS OF FRICTION PAIRS OF BRAKE - Volchenko, Oleksandr; Fidrovska, Natalija; Vasylyshyn, Vitalij; Zhuravlov, Oleksandr; Burava, Oleksandr; Vasylyshyn, Yulija (Problems of Friction and Wear, 2026)
Theoretical and experimental studies of the thermal stability of materials and fluctuations in the friction pair parameters of lifting and transport equipment brakes have revealed the following. The working layers of the lining and the metal friction element are located at different charge poles, but their roles are different: the former act as charge accumulators and undergo profound tribokinetic changes, while the latter act as entropic energy accumulators, i.e., as a battery. Stressful conditions for entropic energy flows include steady-state and thermal stabilization temperatures, as well as the destruction of the surface layers of friction lining materials. Entropy changes related to fluctuations in the friction pair parameters of operating brake devices. Based on the calculated dependence obtained, 3D graphical patterns were constructed to determine the linear wear of the lining for the values of the impulse normal forces, friction path, lining working area, and the hardness of its materials.